The role of psychological empowerment and job satisfaction on turnover intentions directly and indirectly through affective commitment on registered nurses in healthcare industry of twin cities (Islamabad and Rawalpindi) of Pakistan - Rafiq, Nosheen; Syed Haider Ali Shah, Dr.; Sajjad, Shakeel; Ahmed Salem Alyafei, Saleh (International Journal of Engineering and Technology, 2020)
The shift from financial capital to the human capital has brought a significant change in the workplace and market. The role of nurses is getting crucial day by day and there is great need of retention of nurses in order to sustain the smooth operation of hospitals. Nurses’ turnover has gained much importance and has become a concern for the hospitals. Psychological empowerment plays a vital role in retention of the employees and in return leads to success of the organization. Proper psychological empowerment and job satisfaction build such an environment that leads to develop people and enhance their affective commitment in industry like service industry, particularly in healthcare industry where the first impression of an organization is portrayed by their nurses. Researchers and practitioners have paid much of their attention to understand this phenomenon. The aim of the study is to investigate the role of psychological empowerment and job satisfaction on nurses’ turnover intentions directly and indirectly through affective commitment. This study filled the gap by investigating such relationships in healthcare industry which has previously neglected, particularly at nurses level. A total of 520 questionnaires have been distributed in registered public and private hospitals located in twin cities of Pakistan. Structural Equation Modeling (SEM, AMOS) was employed to test hypotheses. This study showed relationships and interesting findings with mediation analysis. Findings of this study are important for top management of hospitals. In order to retain nurses, this study offers the theoretical and practical implications which could be used to enhance the affective commitment of nurses and reduce the turnover intentions.